2020
DOI: 10.3390/nano10112252
|View full text |Cite
|
Sign up to set email alerts
|

2D Octagon-Structure Carbon and Its Polarization Resolved Raman Spectra

Abstract: We predict a new phase of two-dimensional carbon with density functional theory (DFT). It was found to be semimetal with two Dirac points. The vibrational properties and the polarization resolved Raman spectra of the carbon monolayer are predicted. There are five Raman active modes: 574 cm−1 (Eg), 1112 cm−1 (B1g), 1186 cm−1 (B2g), 1605 cm−1 (B2g) and 1734 cm−1 (A1g). We consider the incident light wave vector to be perpendicular and parallel to the plane of the carbon monolayer. By calculating Raman tensor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…Molec-017403-3 ular dynamics simulations also indicate that octagraphene can hold stability even at a high temperature. [18,22,[42][43][44] The mechanical properties of octagraphene are also similar to those of graphene according to previous reports. [22,33,45,46] As it has a C 4v symmetry, two independent elastic constants are 296 N/m and 46 N/m, respectively.…”
Section: Mechanical Stabilitysupporting
confidence: 87%
“…Molec-017403-3 ular dynamics simulations also indicate that octagraphene can hold stability even at a high temperature. [18,22,[42][43][44] The mechanical properties of octagraphene are also similar to those of graphene according to previous reports. [22,33,45,46] As it has a C 4v symmetry, two independent elastic constants are 296 N/m and 46 N/m, respectively.…”
Section: Mechanical Stabilitysupporting
confidence: 87%
“…It is a semiconductor for narrow quasi-one-dimensional (1D) nanoribbons but is a metal for wide nanoribbons and 2D monolayers. Similar structures for carbon and BN have been proposed/predicted or treated theoretically. Motivated by the recent, experimental work by Fan et al, we performed an extensive theoretical study not only on carbon in ohs structure but also on ohs monolayers of group IV elements (Si, Ge) and group IV–IV (SiC, GeC, SnC), III–V (BN, BP, BAs, BSb, AlN, AlP, GaN, InN), and II–VI (ZnSe) compounds and their multilayers as well as three-dimensional (3D) periodic ohs crystals.…”
Section: Introductionsupporting
confidence: 66%
“…The square/octagon structure [26,27] has attracted a lot of attention in the past. He and Wang predicted two Dirac points for the square/octagon structure of carbon and investigated the vibrational properties of the carbon monolayer and its Raman spectrum [28]. In the same year, Wu et al predicted the TE properties of so-Bi, and their results showed that the TE figure of merit of so-Bi can reach a maximum of 0.97, which is higher than that of bismuth monolayer [29].…”
Section: Introductionmentioning
confidence: 99%